The Application of Geographical Information System Technology to the study of Aedes albopictus (Skuse) breeding sites and its implication to Dengue transmission (in Lundu district, Sarawak) - Cheah, Whye Lian (Universiti Malaysia Sarawak, (UNIMAS), 2002)
Dengue fever (D~ J ana Dengue haemorrhagic fever (DHF) are gaining an ever.increasing foothold in Asia and the Americas. The present Aedes vector surveillance system and the use of "classical" Aedes indices remains an issue to resolve. Geographical Information System (GIS) is thought to be a new Aedes surveillance tool with the most potential as the data management system can gather all the information needed for dengue outbreak prediction, This study used GIS technology on Aedes albopictus in the rural dengue transmission area of Lundu District, Sarawak to achieve two main goals : a) To elucidate the association of various risk factors with dengue cases reported in Lundu district, 1999, and b) to design and develop a dengue surveillance system for the monitoring the vector Ae. albopictus in potential outdoor breeding sites.